Pharmaceutical Jargons Used in Pharmaceutical Service of Apotek Wahana Medika Bekasi - Sumartini, Tutut; Ratmo (PROSIDING SENANTIAS: Seminar Nasional Hasil Penelitian dan Pengabdian kepada Masyarakat, 2024)
This study aims to find out the use of jargons in pharmaceutical service of Apotek Wahana Medika Bekasi and to analyze the social context underlaying the use of jargons in the communication between the pharmacists and doctors, and other clinical workers. This study is a descriptive qualitative as it tries to reveal the use of jargons as one of the language varieties in sociolinguistic field. Language variety refers to a set of communicative forms and norms for their use that are restricted to a particular group, community or activities. Pharmaceutical jargons are specific vocabulary or expressions used by pharmaceutical staffs in their communication. This kind of expression is essential to ease communication between them but it might not be understood by common people outside their community. The object of this study is pharmacists, doctors, and pharmaceutical workers who involve in the pharmaceutical service of Apotek Wahana Medika Bekasi. It is assumed that they use specific language suspected to be their jargon. To collect the data, observation and interview were conducted and recorded. Besides, relevant document suspected to contain jargons were reviewed. The data findings revealed the use of jargons and their social contexts in the communication among the pharmacists. As pharmaceutical jargons are their specific terms in their work setting, they are part of English for Occupational Purpose (EOP). The knowledge of these terms, their meaning and social contexts are worth analyzing. Further, the study of specific terms such as jargon might be used as research or material development of training program or for higher school of pharmacy.